Qur'anic Perspective on Social Religious Conflict Resolution Based on Culture of Togetherness and Rembugan in Indonesia - Mukhtar, Naqiyah; Triana, Nita (Al-Hayat: Journal of Islamic Education, 2023)
This study described the resolution of religious and social conflicts in Bantarkawung, Central Java, Indoensia; its contributing factors and how they aligned with the Qur'an's perspective. This study employed a qualitative approach by conducting interviews with participants in conflict resolution. During the Covid-19 period from 2020 to 2021, we collected data. This study found that the local government and religious leaders resolved conflicts based on the culture of togetherness in religious rituals and social works, fostering interactions and adhering to consensus-based "rembugan" to accept differences in religious understanding, particularly regarding ?l?l-amr. In this region, conflicts were typically resolved through conciliation, with a conciliator initiating the process. Additionally, the conciliator actively devised and formulated resolution steps for the disputing parties. This resolution was a combination of ?ul? (reconciliation) and ta?k?m (arbitration), according to the Qur'an. However, this research had limitations; consequently, it is necessary to conduct similar studies in other regions of Indonesia with distinct characteristics from the research area. Comparative studies would also be useful with countries that share similarities with Indonesia, such as Malaysia, Brunei Darussalam, and Singapore and those that differ, such as Middle Eastern, Australian, American, and European nations.